Structural stability of conducting oxide CaRuO3 at high temperatures - Ranjan R.; Senyshyn A.; Vashook V.; Niewa R.; Boysen H.; Frey F. (My University, 2025)
The structure of conducting oxide CaRuO3 has been studied as a function of temperature up to 1300°C by neutron powder diffraction. The structure is found to remain orthorhombic, in space group Pbnm, over the entire temperature range. The structural rigidity is evidenced by the fact that the octahedral tilt angles change by only ∼3° over the entire temperature range. The absence of any structural phase transition in this temperature range and retention of its conducting properties make CaRuO3 more useful compared to its counterpart SrRuO3 with regard to its application as metallic-interface/electrode/substrate material in epitaxial thin film devices to be used at high temperatures. © 2007 American Institute of Physics.